Shaping identities in a holy land - Fishhof, Gil, author.
1 online resource (xiii, 361 pages)
Keywords: "In the 88 years between its establishment by the victorious armies of the First Crusade and its collapse following the disastrous defeat at Hattin, the Latin Kingdom of Jerusalem was the site of a vibrant artistic and architectural activity. As the crusaders rebuilt some of Christendom's most sacred churches, or embellished others with murals and mosaics, a unique and highly original art was created. Focusing on the sculptural, mosaic and mural cycles adorning some of the most important shrines in the Kingdom (such as the Church of the Holy Sepulchre, The Basilica of the Annunciation and the Church of the Nativity) this book offers a broad perspective of Crusader art and architecture. Among the many aspects discussed are competition among pilgrimage sites, crusader manipulation of biblical models, the image of the Muslim, and others. Building on recent developments in the fields of patronage studies and reception theory, the book offers a study of the complex ways in which Crusader art addressed its diverse audiences (Franks, indigenous Eastern Christians, pilgrims etc.), while serving the intentions of its patrons. Of particular interest to scholars and students of the Crusades and of Crusader art, as well as scholars and students of medieval art in general, this book will appeal to all those engaging with intercultural encounters, acculturation, Christian-Muslim relations, pilgrimage, the Holy Land, medieval devotion and theology, Byzantine art, reception theory and medieval patronage"--